Term Paper on The Nature of Cyber Crime and Cyber Threats: A Criminological Review - Mozid Ashraful; Yesmen Nelufer (Journal of Advanced Forensic Sciences, 2020)
Cybercrime is one of the fastest-growing criminal activities in contemporary age. The first recorded cybercrime happened in France in the year 1820. It was not as sophisticated as cybercrime we know in our world today, but, still, that was a crime. Cybercrime has evolved globally as the online platform is progressing. While progress is made in the battle against cybercrime there still remains a wide gap in the consistency of laws across international borders. The main objectives of this study are to explore the nature of cybercrime in developing countries, find out the cyber threats for terrorist activities and explain cybercrime and threats from criminological aspects. This is a descriptive study which is based on secondary data. This study is based on previous researches & studies. this paper discusses the nature of cybercrime in developing countries. It could allow developed countries to understand better the national and international effects of that cyber threats, to determine the conditions of current regional and international agreements, and to help countries create a sound legal framework. And then we notice the impact of cyber threats all over the world. At last, we discuss cybercrime from criminological point of view. Cybercrime is not limited to two neighboring countries and cross-border conflicts; an attempt could be conducted from another world. It is fearful to see cyber wars as the easiest way to carry out sabotaging rather than wars such as cold war, chemical and biological wars, terrorist wars or jihadist attacks. The international legal framework aims by the International Criminal Court to keep offenders accountable for their actions. The government has by far the biggest burden and obstacle in raising knowledge of cybercrime among the people.
Keywords: Cybercrime